The Cognitive-Pedagogical Link: Working Memory Strategies and The Enhancement of Qur’an Memorization and Retention - Mohammad Syairozi Dimyathi; Hannanah Mukhtar Thabrani; Nurhan Mohammad Syairozi; Waskito Wibowo; Fatihunnada Fatihunnada (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
Memorization of sacred texts, particularly the Qur’an (Hifz), is a vital global pedagogical practice in Islamic education, yet institutions consistently face challenges related to variations in students’ memorization speed and the durability of retention. These inconsistencies stem from varying individual cognitive capacities. This study aims to identify, apply, and evaluate the effectiveness of targeted working memory strategies in enhancing cognitive capacity and optimizing both the immediate memorization and long-term retention of Qur’anic content among students. Employing a quantitative approach, the study recruited 32 participants from the Faculty of Dirasat Islamiyah at Syarif Hidayatullah State Islamic University in Jakarta. Data were analyzed using non-parametric statistical tests, specifically the Wilcoxon signed-rank test, Mann-Whitney U-test, and Kruskal-Wallis test, alongside descriptive statistics, to compare pre- and post-intervention memorization and retention scores. The findings indicated a statistically significant difference between the mean pre-test and post-test scores, accompanied by a medium effect size, confirming the strategies’ immediate efficacy. Crucially, the decrease in scores between the post-test and subsequent retention measurement was significantly smaller than the decrease between the pre-test and initial retention measurement. The memorization strategy model used effectively enhances working memory function and significantly improves both initial learning and retention rates. This research strongly recommends the application of this strategy model within Islamic educational institutions to optimize students’ Hifz performance, bridging the gap between traditional practices and cognitive-pedagogical advancements.